Aqueous emulsion polymerizations of methacrylates and styrene via reversible complexation mediated polymerization (RCMP). Issue 40 (28th September 2021) - Mao, Weijia; Sarkar, Jit; Peng, Bo; Goto, Atsushi
Abstract : Aqueous emulsion polymerization via reversible complexation mediated living radical polymerization yielded low-dispersity poly(methyl methacrylate)s and polystyrenes. Abstract : Reversible complexation mediated polymerization (RCMP) was successfully exploited in aqueous emulsion polymerization of methyl methacrylate (MMA). The polymerization behavior was comprehensively studied using a series of emulsifiers, alkyl iodide initiating dormant species, and catalysts. The optimized combination of these species generated stable polymer particles with relatively high solid contents (up to nearly 50%) and achieved nearly quantitative initiation efficiency and low dispersity ( Đ = 1.1–1.3). The kinetic and mechanistic aspects of the polymerization were elucidated by partitioning tests of the species in aqueous and organic phases and the particle number analysis in the course of polymerization. The emulsion RCMP was amenable for not only MMA but also functional methacrylates and styrene. No use of transition metal or sulfur compounds, relatively high solid contents, good monomer versatility, and high chain-end fidelity achievable in the emulsion RCMP are attractive features for polymer materials applications and industrial applications.